KAJIAN KESENJANGAN KETERSEDIAAN LAHAN DAN POTENSI PENGEMBANGAN PERTANIAN DI WILAYAH TENGGARONG SEBERANG - Sopian, Akhmad; Noor, Rustam Baraq (Universitas Wahid Hasyim, 2022)
This study examines the gap between land availability and agricultural land potential to support food security with two approaches, namely land carrying capacity and land availability. This study uses a survey method by describing an object of study. Data collection and inventory consisting of primary data from surveys and observations in the field as well as secondary data. Secondary data includes data on actual commodity production, base maps and thematic maps, including land use maps, slope maps, and land maps. The results showed that the gap in the availability of agricultural land occurred because the land was used for other uses, namely bush mining. The land characteristics in Tengarong Seberang District are hilly and steep with a slope domination of 26-40% so that most of them lack the potential for agricultural development. There are eight villages that have not been able to be self-sufficient in food due to low land carrying capacity. Embalut, Loa Ulung, and Separi villages have the potential to become food self-sufficiency villages with optimal land management for lowland rice fields.